plz solve with solution
Attachments:
![](https://hi-static.z-dn.net/files/d4a/388477315df95ad8294378b9291b9122.jpg)
Answers
Answered by
0
.
Step-by-step explanation:
The equation to proved is:
Given:
Compute the value of right hand side of the equation as follows:
Compute the value of left hand side of the equation as follows:
The RHS ≠ LHS
Thus, .
Answered by
0
Answer:
no
Step-by-step explanation:
LHS:
=(x-y)-z
=(2/5-(-1/5))-4/5
=3/5-4/5
= -1/5
RHS:
=x-(y-z)
=2/5-(-1/5-4/5)
=2/5+1
=7/5
Similar questions